The art of faith : a guide to understanding Christian images - Couchman, Judith, 1953- (Brewster, Massachusetts : Paraclete Press, 2012)
"Judith Couchman, art history instructor at the University of Colorado at Colorado Springs, unfolds the fascinating (and sometimes mysterious) world of Christian imagery through the ages. This comprehensive guidebook is practical and easy to read, and includes illustrations"--
The art of faith -- The Holy Trinity -- The unseen world -- Faithful followers -- Sacred symbols -- Liturgical art.
Includes indexes.
Keywords: Christian art and symbolism